Simulasi Perbandingan Perhitungan Kredit Bank Konvensional dan Bank Syariah dengan MATLAB - Luthfiani Yasyifa; Onoy Rohaeni; Yurika Permanasari (Bandung Conference Series: Mathematics, 2022)
Abstract. The development of the banking world is increasingly showing progress, especially with the emergence of Islamic banking in addition to conventional banking. The existence of this type of bank is equally aimed at boosting the economy and strengthening economic stability. These two banks certainly have differences in their operations, especially in terms of comparing the implementation of credit agreements and their calculations for conventional banks and Islamic bank financing. This study aims to determine the comparison of calculations and policies on conventional banks and Islamic banks in providing credit to customers. Islamic banks use murabahah contracts, namely contracts with a buying and selling system and the bank takes advantage of the agreement between the seller and the buyer. Meanwhile, conventional banks use interest on the principle of borrowing and borrowing or credit. The results showed that the sliding rate with a decreased profit margin obtained the amount of the difference in interest of 24.28%. Flat rates with flat profit margins have the same total interest, while in annuities there is a difference of 3.9%. Of the three methods, the profit margin of Islamic banks is higher than that of conventional banks. This is because Islamic banks have an agreement or at the beginning so that the margin will not change. Whereas in conventional banks, interest rates will fluctuate following the Basic Loan Interest Rate (SBDK). Abstrak. Perkembangan dunia perbankan semakin menunjukkan kemajuannya, terlebih lagi dengan munculnya perbankan syariah disamping perbankan konvensional. Keberadaan jenis bank ini sama-sama bertujuan untuk mendorong perekonomian serta memperkuat stabilitas ekonomi. Kedua bank ini tentu memiliki perbedaan dalam operasionalnya, khususnya dalam masalah perbandingan pelaksanaan perjanjian kredit dan perhitungannya pada bank konvensional dan pembiayaan bank syariah. Penelitian ini bertujuan untuk mengetahui perbandingan perhitungan dan kebijakan pada bank konvensional dan bank syariah dalam memberikan kredit kepada nasabah. Bank syariah menggunakan akad murabahah yaitu akad dengan sistem jual beli dan bank mengambil keuntungan atas kesepakatan antara penjual dan pembeli. Sedangkan pada bank konvensional menggunakan bunga dengan prinsip pinjam meminjam atau kredit. Hasil penelitian menunjukkan hasil sliding rate dengan margin keuntungan menurun diperoleh jumlah selisih bunga sebesar . Flat rate dengan margin keuntungan flat memiliki total bunga yang sama, sedangkan dalam anuitas terdapat selisih sebesar . Dari ketiga metode, margin keuntungan pada bank syariah lebih besar dibanding dengan kredit bunga pada bank konvensional. Hal tersebut dikarenakan bank syariah memiliki perjanjian atau di awal sehingga margin tidak akan berubah. Sedangkan pada bank konvensional, suku bunga akan berfluktuasi mengikuti Suku Bunga Dasar Kredit (SBDK).